Video In Situ Snowfall Sensor (VISSS) data for Hyytiälä (December 2023 - July 2024) - Maximilian Maahn; Dmitri Moisseev; Nils Pfeifer (PANGAEA, 2025)
The open source Video In Situ Snowfall Sensor (VISSS) is a novel instrument for the characterization of particle shape and size in snowfall. The VISSS consists of two cameras with LED backlights and telecentric lenses that allow accurate sizing and combine a large observation volume with relatively high resolution and a design that limits wind disturbance. Here, movies and images of falling precipitation particles are provided for station Hyytiälä in December 2023 - July 2024. For further details on the VISSS instrument see Maahn et al. (2024).